(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Objective: To assess the factors of metabolic syndrome (MetS) in post menopausal women in Bangladesh. Methods: Menopausal women are at increased risk of metabolic syndrome (MetS). This cross-sectional study on 64 willing post menopausal women from an urban and a rural area of Bangladesh was done. The socio-epidemiologic factors with anthropometric examination, blood pressure recording and fasting blood analysis for triglyceride (TG), high density lipoprotein (HDL), sugar were studied. Results: Prevalence of MetS was 50.0% (95% CI= 39.9%- 60.1%) among menopausal women, seventy five percent of them were urban. Low HDL cholesterol prevailed in almost 96% respondents followed by high TG (51%), obesity (28.0%), high fasting blood sugar (FBS, 27.1%) and hypertension (HTN, 16.9%). On logistic regression, age (OR=1.6, 95% CI: 1.3-1. 9), male sex (OR=2.5, 95% CI: 1.4-4.2) and exercise (OR=1.9, 95% CI: 1.2-2.9) produced significantly higher odds of being associated with MetS; rural area (OR=1.4, 95% CI: 1.0-2.1) and sedentary occupation (OR=1.7, 95% CI: 0.9-3.0) were associated just insignificantly. Though higher income, better education, good physical movement and knowledge of MetS produced protective odds, they were not significant. Conclusions: The study suggests that MetS is highly prevalent among Bangladeshi menopausal women. Further studies are needed to identify risk factors and for effective preventive measures to control this metabolic disease. J Bangladesh Coll Phys Surg 2016; 34(1): 15-20